2018
DOI: 10.1590/2177-9465-ean-2017-0288
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of illness and human cost at work in a psychiatric hospital

Abstract: Objective: To investigate the risk of illness and to the human cost at work from the point of view of the nursing team of a psychiatric hospital. Method: A cross-sectional study performed in a psychiatric hospital with 74 nursing workers. The Human Cost of Labor Scale was applied. Results: In the evaluation of the human cost at work, the cognitive cost factor was evaluated as a critical risk for the sickness of the nursing worker, while the factors affective cost and physical cost demonstrated a satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…That is, it is a field where professional frustration is common because of the results, sometimes out of reality and without a precise prognosis, in a context in which cognitive demands are high, revealing risk of workers' illnesses. (27,37) However, even in the face of the discussions presented in this study, it cannot be said that there are relations between CMD and the fact that the sample comes from a psychiatric hospital, because, among the work variables, only the professional category presented statistical significance.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…That is, it is a field where professional frustration is common because of the results, sometimes out of reality and without a precise prognosis, in a context in which cognitive demands are high, revealing risk of workers' illnesses. (27,37) However, even in the face of the discussions presented in this study, it cannot be said that there are relations between CMD and the fact that the sample comes from a psychiatric hospital, because, among the work variables, only the professional category presented statistical significance.…”
Section: Discussionmentioning
confidence: 65%
“…(26) A study with nursing workers at a psychiatric hospital has shown, for example, that controlling emotions, making continuous and repetitive use of sight, memory, hands, and feet, and dealing with the aggressiveness of others are critical conditions for becoming ill, and require constant attention. (27) Another alarming situation pointed out in nursing was the situation of working in two different places, due to the low salaries, ease to conciliate the various employment bonds, and the permissiveness of labor laws. (28) These conditions contribute to the high physical and mental load of nursing work, demonstrating the need for rest breaks and leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the ECHT, we note that it had a critical risk classification for the affective, cognitive, and physical cost factors (table 2), indicating an extreme situation with negative cost and labor distress. Such results signal a warning when compared with data from the application of ECHT to nursing workers in a reference psychiatric hospital in Teresina, Piauí 17 .…”
Section: Weak Employment Contracts Imply Changing Professionals This ...mentioning
confidence: 86%
“…Inadequate working conditions and care for people with mental disorders with considerable cognitive demand represent critical risks for the illness of nursing workers (6)(7) . Night work, a common situation among these workers, is a strong factor of occupational exposure, generating important consequences for the work activity and health conditions of the worker (8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results of care -sometimes out of reality -, the state of continuous surveillance and professional dissatisfaction related to environmental structure, comfort, safety and wages should potentiate the possibilities of illness (7,10) .…”
Section: Introductionmentioning
confidence: 99%